PERANCANGAN SISTEM INFORMASI AKUNTANSI PENGENDALIAN INTERN PIUTANG TAK TERTAGIH DENGAN METODE UMUR PIUTANG PADA BPR SEJAHTERA ARTHA SEMBADA - isnayati isnayati (LPPM Universitas Sains dan Teknologi Komputer, 2023)
This research aims to determine the implementation of internal control in minimizing bad debts at BPR Sejahtera Artha Sembada Brangsong. The information system used is not yet effective. There is no customer data regarding late payment of receivables. The aim of this research is design. Accounting Information System for Internal Control of Receivables at BPR Sejahtera Artha Sembada Brangsong, with the benefit of making it easier for employees to check customer arrears who have not paid receivables in order to maximize collections. In accordance with the research objectives, this research was carried out using the aging of accounts receivable method and creating a web-based Information System using the PHP and MySQL programming languages.